Does correctional supervision of amphetamine users reduce the risk of re‐offending?. (13th December 2020) - Weatherburn, Don; Yeong, Steve
Abstract: Aim: To examine the specific deterrent effect of offender supervision on the risk of a further offence by persons convicted of amphetamine use and/or possession. Design: Observational study of two groups matched on a wide range of factors using augmented inverse probability of treatment weighting. Setting: New South Wales (NSW), Australia. Participants: A total of 2099 persons convicted of amphetamine use and/or possession and placed on either a supervised good behaviour bond (1004) or a bond without supervision (1096). Measurements: Conviction for another amphetamine use/possession offence, any drug offence, assault or theft within 48 months free time after the index court appearance. Findings: Only two of the treatment estimates were consistent with a deterrent effect. Where the outcome was an assault offence, the estimated reduction in risk of re‐offending was 1%. Where the outcome was a theft offence, the estimated reduction in the risk of reoffending was 0.07%. Neither result was statistically significant. The coefficients measuring the effect of supervision on the remaining two outcomes (use/possess amphetamine and use/possess any drug) were both positive and not statistically significant. Conclusion: Correctional supervision does not appear to have been effective in New South Wales, Australia, in reducing the risk of reoffending among people convicted of amphetamine use/possession.